Neuralgic amyotrophy with cervical root and cranial nerves involvement in a child - Ashrafi, Mahmoud Reza; Tavasoli, Alireza; Ghahvechi-Akbari, Masood (Iranian Journal of Child Neurology, 2019)
Idiopathic neuralgic amyotrophy (INA) is a disorder presented with acute severe pain in the upper extremity, followed by muscle weakness, paralysis and atrophy. INA is rare in children and few reports are found in the literature. Here, we report a case of INA in an 8-year old boy following pharyngitis.